Comparison of molecular species identification for North Sea calanoid copepods (Crustacea) using proteome fingerprints and DNA sequences. (13th July 2013) - Laakmann, S.; Gerdts, G.; Erler, R.; Knebelsberger, T.; Martínez Arbizu, P.; Raupach, M.J.
Abstract: Calanoid copepods play an important role in the pelagic ecosystem making them subject to various taxonomic and ecological studies, as well as indicators for detecting changes in the marine habitat. For all these investigations, valid identification, mainly of sibling and cryptic species as well as early life history stages, represents a central issue. In this study, we compare species identification methods for pelagic calanoid copepod species from the North Sea and adjacent regions in a total of 333 specimens. Morphologically identified specimens were analysed on the basis of nucleotide sequences (i.e. partial mitochondrial cytochrome c oxidase subunit I (COI) and complete 18S rDNA) and on proteome fingerprints using the technology of matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS). On all three molecular approaches, all specimens were classified to species level indicated by low intraspecific and high interspecific variability. Sequence divergences in both markers revealed a second Pseudocalanus species for the southern North Sea identified as Pseudocalanus moultoni by COI sequence comparisons to GenBank. Proteome fingerprints were valid for species clusters irrespective of high intraspecific variability, including significant differences between early developmental stages and adults. There was no effect of sampling region or time; thus, trophic effect, when analysing the whole organisms, was observed in species‐specific protein mass spectra, underlining the power of this tool in the application on metazoan species identification. Because of less sample preparation steps, we recommend proteomic fingerprinting using the MALDI‐TOF MS as an alternative or supplementary approach for rapid, cost‐effective species identification.